Pembuatan Ready To Wear Fantasy The New Srikandhi Style Excotic Dramatic Menggunakan Pendekatan Semiotika - Mien Zyahratil Umami; Riris Kesawamurti Anggarani (Garina, 2022)
Clothing is a cultural phenomenon that cannot be separated from the meaning of signs. It can be studied using a semiotic approach. A fantasy dress with the source of the Srikandhi puppet idea was associated with a fashion meaning. The purpose of this final project was to know the process of making ready to wear fantasy the new Srikandhi exotic dramatic style using a semiotic approach. The method used in this research was qualitative method. The data collection techniques used were observation, literature, interviews, and documentation. The process of making ready to wear fantasy, the new Srikandhi exotic dramatic style includes; determine fashion design, fashion design analysis, preparation of tools and materials, determine sizes, basic pattern making, material cutting, exhibitions, ironing of upholstery materials, process of sewing clothes, and finishing. Making ready to wear fantasy, the new Srikandhi exotic dramatic style using a semiotic approach must pay attention to various elements, such as designs, motifs, colors, and accessories so that it can be meaningful. The suggestions of this Final Project were; in making fantasy clothing should not eliminate the characteristics of the source of the idea. So that clothing can be created that matches the source of the idea.